Novo método analítico para determinação do fármaco 5- fluorouracil na presença de alfa-ciclodextrina - SENA, Guilherme Azevedo de (2024)
5-Fluorouracil (5-FLU) is one of the most used drugs in the treatment of cancer, a disease characterized by the unbridled proliferation of abnormal cells. This disease is one of the main causes of death in the world, especially breast and colorectal cancer. In this context, considering the importance of this drug for the treatment of cancer, it is proposed to develop a new analytical method for its determination. To this end, a boron-doped diamond electrode – DDB was used as a working electrode and a cyclodextrin, Alpha-Cyclodextrin (α-CD), for better detection of 5-FLU. In this sense, the proposed method presented a higher peak current for the analyte in the presence of α-CD, compared to its response in the absence of this biomolecule supposedly due to the formation of an inclusion complex (5-FLU:α-CD). The measurements were carried out using Cyclic Voltammetry (VC), optimizing the evaluated parameters, such as α-CD concentration, pH and supporting electrolyte to obtain the analytical curve. The results obtained for drug analysis in the presence of α-CD showed a relative standard deviation, DPR, equal to 2.38% for measurements carried out on different days, which suggests satisfactory stability and reproducibility of the material on the surface of the DDB electrode. The proposed method presented two analytical curves for 5-FLU determination in the presence of 4 mM of α-CD: one from 50 to 2,000 μM and the other from 3000 to 6000 μM. The limits of detection (LD) and quantification (LQ) of 8.52 µM and 28.40 µM, respectively. The proposed method was applied to determine 5-FLU in an artificial urine samples, presenting average recovery value of 97,5%